Secretion of IL-1β From Monocytes in Gout Is Redox Independent - Alberts, Ben M.; Bruce, Connor; Basnayake, Kolitha; Ghezzi, Pietro; Davies, Kevin A.; Mullen, Lisa M. (Frontiers in Immunology, 2019)
The proinflammatory cytokine interleukin-1β (IL-1β) plays important roles in immunity but is also implicated in autoimmune disease. The most well-established mechanism of IL-1β secretion is via activation of the NOD-like receptor family pyrin domain containing-3 (NLRP3) inflammasome which requires an initial priming signal followed by an activating signal. However, the precise mechanism by which the inflammasome is activated remains unclear. The role of reactive oxygen species (ROS) in this process is contradictory, with some studies suggesting that ROS are crucial while others describe opposite effects. In this study, we evaluated the effects of oxidative stress on IL-1β secretion. Gout is a disease driven solely by IL-1β secretion in response to monosodium urate (MSU) crystals which form during periods of hyperuricemia and thus presents an opportunity to study factors contributing to IL-1β secretion. Sera and monocytes were isolated from patients with gout to determine whether differences in antioxidant status could explain the susceptibility of these individuals to gout attacks. In addition, sera and monocytes were collected from patients with chronic kidney disease (CKD) for comparison as this condition is associated with high levels of oxidative stress and disturbances in serum uric acid levels. There were differences in some aspects of antioxidant defenses in gout patients and these were mainly due to higher serum uric acid. Monocytes from gout patients were more responsive to priming, but not activation, of the NLRP3 inflammasome. However, expression of the components of the NLRP3 inflammasome were unaffected by priming or activation of the inflammasome, nor were these expression levels differentially regulated in gout patients. Inhibition of ROS by N-Acetyl Cysteine inhibited TLR2-induced priming of the NLRP3 inflammasome, but had no effect on MSU-induced activation. Together these findings demonstrate that oxidative stress only affects priming of the NLRP3 inflammasome but does not influence activation.